Arrested Puberty in an Adolescent Male with Anorexia Nervosa Successfully Resumed with Multidisciplinary Care - Diana Simão Raimundo; Carolina Figueiredo; Ana Raposo; Bernardo Dias Pereira (Case Reports in Pediatrics)
The normal development of puberty depends on the specific pulsatility of gonadorelin, which is finely regulated by genetic and environmental factors. In the published literature, eating disorders figure as a cause of pubertal delay/arrest in females but are rarely considered in males with disordered puberty. A 16.7-year-old male was referred to the Department of Pediatrics with arrested puberty due to severe malnutrition in the context of food restriction. Past medical history was relevant for asthma. Generalized cachexia, facial lanugo hair, cutaneous xerosis, and Russell’s sign were noted; he had a height of 155.5 cm (−2.5 SD; target height: 168 cm, −1.1 SD) and a BMI of 12.4 kg/m2 (−6.8 SD); left and right testicular volumes were 8 mL and 10 mL, respectively. He had a twin brother who had normal auxological/pubertal development (height: 167 cm, −1.05 SD; testicular volumes: 20 mL). Anorexia nervosa was diagnosed, and he was enrolled in a personalized treatment and surveillance program. “Nonthyroid illness” resembling secondary hypothyroidism was noted, as was low bone mineral density. Clinical and biochemical follow-up showed significant improvements in BMI (16.2 kg/m2, −2.55 SD), completion of puberty (testicular volumes: 25 mL), and reversion of main neuroendocrine abnormalities. Herein, we present an adolescent male with arrested puberty in the context of anorexia nervosa. The recognition of this rare condition in males allows a personalized approach to disordered puberty, with resumption of normal function of the hypothalamic-pituitary-gonadal axis and achievement of pubertal milestones.